RELIABILITY ESTIMATION FOR TWO PARAMETERS LOG-LOGISTIC DISTRIBUTION - Salih, MakkiÃ‚Â A.Ã‚Â MohammedÃ‚Â ; J.Ã‚Â Kamees, AhmedÃ‚Â (MAGISTRA, 2017)
InÂ thisÂ paper,Â weÂ studyÂ twoÂ parametersÂ Log-LogisticÂ distribution,Â appliedÂ twoÂ estimationÂ methods(MomentÂ MethodÂ (MOM)Â andÂ ModificationÂ MomentÂ MethodÂ (MM))Â toÂ estimateÂ parametersÂ andÂ reliabilityfunctionÂ forÂ thisÂ distribution.WeÂ usedÂ theÂ simulationÂ toÂ generateÂ randomÂ dataÂ followÂ theÂ distributionÂ onÂ threeÂ modelsÂ ofÂ theÂ realÂ valuesofÂ theÂ parameters:Â )4,5(:),5.3,5.1(:),3(: 321 ï½ï½ï½ï½ï½ï½ ï¢ï¡ï¢ï¡ï¢ï¡ AAA withÂ samplesizeÂ (nÂ =10,25,50,75,100)Â andÂ replicateÂ sampleÂ (N=1000),Â andÂ takingÂ fiveÂ differentÂ failureÂ timesÂ forÂ eachÂ caseÂ toestimateÂ reliabilityÂ function.ComparisonsÂ haveÂ beenÂ madeÂ betweenÂ theÂ obtainedÂ resultsÂ fromÂ theÂ estimatorsÂ usingÂ theÂ MeanÂ SquareErrorsÂ (MSE),Â theÂ resultsÂ indicateÂ that:-TwoÂ parametersÂ estimatorsÂ ofÂ (MM)areÂ betterÂ thanÂ estimatorsÂ ofÂ (MOM),Â andÂ theÂ reliabilityÂ estimatorsofÂ (MOM)areÂ betterÂ thanÂ estimatorsÂ ofÂ (MM).Keywords: LogâLogistic distribution, Moment Method, Modification Moment Method